Activity Guidelines to Promote Desirable Citizenship Characteristics of Sports School Students, The Institute of Physical Education - tammajee, jarinya; Wannapaisan, Chetthapoom; Mangkhang, Charin (Academic Journal of Thailand National Sports University, 2018)
This research has the purpose of studying how to organize Activity Guidelines to promote a desirable citizenship and the desirable citizenship of students in sports schools at the Institute of Physical Education. The target groups in the research were the administrators and teachers of Lampang Sports School and Nakhon Sawan Sports School from the Institute of Physical Education in the North region Sports School. Two schools are divided into 7 administrators and 83 teachers with a total of 90 people. Sampling was obtained by a selective method. The instrument was a questionnaire, dividedinto 4 parts, Data analysis were frequency, percentage, mean and standard deviation. The study results found that: 1) Activity guidelines to promote desirable citizenship characteristics of Sports School Students, The Institute of Physical Education was found to be at a high level. When considering each aspect, it was found that it was high at all four levels. Data was sorting by the level of activity guidelines to develop desirable citizenship attributes in descending order.This includes the development of secondary development activities, the instilling desirable features by incorporating in daily routines, integration in the subject matter and project management to develop desirable attributes, respectively. 2) Desirable citizenship students of Sports School under the jurisdiction of the Institute of Physical Education. It is found to be at a high level. The highest level of desirable citizenship starting was patriotism, religion and royal family. The desirable qualification of citizenship was at the high level in public mind, spirituality, discipline, honesty, sufficient life, consciousness, Thainess and working inspiration respectively.